CORRELATION OF FLI FATTY LIVER INDEX WITH INSULIN RESISTANCE INDICES IN PATIENTS WITH METABOLIC SYNDROME - Mitrović, Marija; Misevic, Vojko (Medicinski podmladak, 2023)
CORRELATION OF FLI FATTY LIVER INDEX WITH INSULIN RESISTANCE INDICES IN PATIENTS WITH METABOLIC SYNDROME Аuthor: Marija Mitrović, Vojko Mišević e-mail: mitrovicmarija505@gmail.com, misevic.vojko@gmail.com Mentor: TA Ljiljana Popović, Clinic for Endocrinology, Diabetes and Metabolic Diseases, University Clinical Centre of Serbia e-mail: liliana.popovich@gmail.com Introduction: Metabolic syndrome includes insulin resistance, visceral obesity, hypertension and dyslipidemia, which together lead to increased risk of atherosclerosis, cardiovascular diseases, diabetes mellitus. Insulin resistance is considered a pathophysiological mechanism underlying metabolic syndrome, characterized by inadequate glucose metabolism, hyperinsulinemia and lipid imbalance. Non-alcoholic fatty liver disease is a chronic disease characterized by microvesicular steatosis and isn’t consequence of the use of drugs, alcohol or inherited diseases and is hepatic manifestation of metabolic syndrome. The Aim: Since insulin resistance is pathophysiologically related to metabolic liver diseases, the aim of this study was to investigate correlation of the FLI index with insulin resistance indices (HOMA, Tyg, QUICKI) in complete sample, but also at the level of groups of overweight and obese patients. Мaterial and Methods: Study included 70 patients who met the criteria for the diagnosis of metabolic syndrome and who were randomly selected from medical documentations from the Cabinet for lipid disorders and lipopheresis, Clinic for Endocrinology KCS. Patients were divided into two groups. Group A were overweight patients (BMI 25-29.9 kg/m2). Group B were obese patients (BMI>30 kg/m2). Insulin resistance index values were compared between groups and then correlated by statistical analysis with FLI index within groups and in a complete sample. Results: Statistical analysis found correlation between the FLI index and the insulin resistance indices, HOMA and Tyg (p=0.03; p<0.001) in a complete sample. A statistically significant difference in the values of the FLI index between the examined groups was proved (p=0.001). Conclusion: The positive correlation between the FLI index with the Tyg and HOMA indices speaks in favor of the interrelationship between insulin resistance and fatty liver in patients with metabolic syndrome. In this case insulin resistance can be a predictor for the development of non-alcoholic fatty liver disease, steatosis, steatohepatitis, hepatocellular carcinoma and cardiovascular diseases. Кeywords: metabolic syndrome; insulin resistance; FLI index